PENGARUH KEMAMPUAN TEKNIK PERSONAL DAN PARTISIPASI PEMAKAI SISTEM INFORMASI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA ULP PLN WILAYAH BANJARMASIN - Ruslinda Agustina; - Masrifani; Via Amelia Rofika Suri (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, The purpose of this study is to test empirically the effect of personal technical abilities and the participation of users of information systems on the performance of accounting information systems at ULP PLN Banjarmasin region. The method used is a survey method with a sample size of 67 employees who became respondents. The test tool used with the SPSS Version 22.00 for Windows program. The results showed that H1 was rejected with a significant value of 0.276, this is because the respondents still did not have the ability to use the system. The results of the research H2 were accepted with a significant value of 0.000, this is because the respondents felt that they participated in running the information system that was built. Meanwhile, the proposed H3 is accepted with a significant value of 0.000. This research concludes that H1 is accepted and H2 is accepted, which means that H2 affects the performance of the accounting information system at the ULP PLN in Banjarmasin, while simultaneously H3 is accepted, which means that all variables have an effect on the performance of the accounting information system.